2018
DOI: 10.3926/ic.1120
|View full text |Cite
|
Sign up to set email alerts
|

The role of patron dining experience and emotions on relationship quality in chain restaurant industry

Abstract: Purpose: This paper investigates the role of patron dining experience (PDE) and emotions on relationship quality in the chain restaurant industry.Design/methodology: Stratified random sampling method was used where questionnaires were distributed to the respondents in 16 selected ‘Kopitiam’ outlets throughout Malaysia. The empirical findings from 316 customers of those outlets were examined using Partial Least Squares (PLS).Findings: The findings provide strong evidence of the relationships between PDE and emo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…By reviewing previous studies that dealt with the relationship between customer relationship quality in its two dimensions (customer satisfaction and customer trust) and customer loyalty to the organization, we concluded that several studies have proven a positive relationship between customer relationship quality and loyalty to the organization (e.g., Dai et al, 2023;Kuhn & Mostert, 2018;Rahmani-Nejad et al, 2014;Saleem et al, 2018;Ying et al, 2018;Yu & Tseng, 2016). However, no effect was reported between the customer relationship quality and their loyalty to the organization in other studies such as Eakuru andMat (2008), Alejandro et al (2011), Chen and Chen (2017), van de Scheur (2017), andSayil et al (2019).…”
Section: Study Overview (Study Problem)mentioning
confidence: 95%
“…By reviewing previous studies that dealt with the relationship between customer relationship quality in its two dimensions (customer satisfaction and customer trust) and customer loyalty to the organization, we concluded that several studies have proven a positive relationship between customer relationship quality and loyalty to the organization (e.g., Dai et al, 2023;Kuhn & Mostert, 2018;Rahmani-Nejad et al, 2014;Saleem et al, 2018;Ying et al, 2018;Yu & Tseng, 2016). However, no effect was reported between the customer relationship quality and their loyalty to the organization in other studies such as Eakuru andMat (2008), Alejandro et al (2011), Chen and Chen (2017), van de Scheur (2017), andSayil et al (2019).…”
Section: Study Overview (Study Problem)mentioning
confidence: 95%
“…An investigation by (Ying Tuan, et al, 2018), reveal that customer's perception of service quality is overall dining experience, relationship quality, and emotions which positively and significantly builds a good relationship with the service providers. Relationship quality means when customers receive all the service quality components like excellent food, very good service quality, environment, price-value ratio, other convenience factors such as warm welcome, special care, discounts on certain other nationals.…”
Section: Customer Satisfaction and Customer Loyaltymentioning
confidence: 99%
“…The customers' desire to maintain the relationship, satisfaction towards the service provider's past performance and their trusts on the service provider's future performance can be indicated though a strong relationship quality measure (Rajaobelina, 2017;Radovic et al, 2017;Brun, Rajaokelira & Licard, 2014). In general, the relationship quality construct is conceptualized as a multi-dimensional construct consisting of three main dimensions of satisfaction, trust and commitment (Lo et. al.…”
Section: Relationship Qualitymentioning
confidence: 99%
“…However, out of those attributes, only five are commonly accepted in the literature. The attributes are price, food, service, location and environment (Lo et. al., 2018;Haghighi et al, 2012).…”
Section: Patron Dining Experience (Pde)mentioning
confidence: 99%